Diplomatic ambiguity: Cyprus 1961–1963 – how ambivalent diplomatic attitudes, particularly those of the CRO, encouraged dangerous Greek Cypriot attempts to modify the status quo created by the London and Zurich agreements. Issue 1 (2nd January 2022) - Markides, Diana
ABSTRACT: This article will focus on the international relations that the Greek Cypriot leaders sought to build up between 1960 and 1963 as part of an attempt to secure more substantial power for the Greek Cypriot majority on the internal front and a more substantial independence for the new state than the 1960 Treaties allowed. It will analyse the causes for optimism regarding this policy. It emerges that both courses were more dangerous than they may have seemed at the time. The Island's colonial legacy of Commonwealth membership tended to give the Greek Cypriot leadership the impression that there were more possibilities for the promotion of greater substance to majority rule within the Island and more choice in the new Republic's international status than there actually were. In this context, the lack of cooperation between the Foreign Office and the Commonwealth Relations Office resulted in an element of deceptive ambiguity regarding the British position on the Cyprus issue. Archbishop Makarios, the President of the Republic, maintained a positive attitude towards the Commonwealth not least because it allowed Cyprus to belong to an international organisation outside Turkish-Greek protection intended by the guarantor powers. Rauf Denktash, the Turkish Cypriot leader closest to the Turkish government, opposed membership for diametrically opposite reasons.